ANALISIS HUKUM KETENAGAKERJAAN TERHADAP PERMINTAAN BENEFIT THR OLEH MITRA PLATFORM TRANSPORTASI DALAM JARINGAN (ONLINE) - Parlin Bachtiar Sinaga (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
The existence of digital transportation platforms has been increasingly felt by the Indonesian public in recent years. This not only helps users, who are facilitated by online bookings, but also drivers, better known as online motorcycle taxis. More than a million drivers currently rely on online transportation for their livelihoods. This job is considered relatively easy to